Indústrias criativas e os processos de produção e pós-produção de fotojornalismo: análise de um jornal do agreste pernambucano. - Barbosa, Diogenes José Pereira (2020)
The technological resources have been incorporated into the work routines of different companies that produce informative content. In this sense, this study aims to investigate how the appropriation of these tools by professionals working in Jornal Vanguarda, in the municipality of Caruaru (PE), occurs in the production and postproduction stages of photojournalism. In the light of specialized literature on communication, photojournalism and creative industries, for example, as well as semistructured interviews with vehicle professionals, a content analysis is developed. As a result, it is pointed out: the recognition of the changes that have occurred between post-industrial and modern society - and the work systems themselves -, in addition to the way in which people have related to time and space; aspects of changes in consumption, including the communication and information content; weaknesses in the structure that is made available so that professionals can develop images during the productive routine; as well as the need for investments to improve the existing structure and continuous training of employees, allowing them to improve and, of course, deepen their knowledge on the subject.